Make in India versus made in India: Choice of trade policy for India: A Comparative Analysis of Make in India and Atmanirbhar Bharat abhiyaan for Economic Growth and Trade Potential (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Theoretically, the development of manufacturing activity has been associated with economicdevelopment of a country. In order to augment the growth process of the economy, India has undertaken anumber of measures to boost its manufacturing sector as well as give a fillip to external trade. This articleexamines two policies currently being pursued by the government to support the manufacturing sector.The Make in India scheme and the Atmanirbhar Bharat abhiyaan were initiated under differentcircumstances but have a similar goal of increasing India’s economic growth and trade potential. Usingsecondary sources of data, an analysis of the two schemes is discussed in the article